Recursos digitales en el aprendizaje basado en proyectos, en estudiantes de bachillerato técnico, Unidad Educativa Barreiro - Caicedo Bonilla, Esther Mariana (2023)
The present research study on digital resources and project-based learning, has set as general objective: To relate the contributions, digital resources offer, to project-based learning, in technical high school students of Barreiro Educational Unit, for which it will be sought to develop a type of basic research the same that allows the theoretical verification through bibliographic sources of study, as well as a non-experimental research design, where it will not proceed to the manipulation of the data that will be obtained from the surveys and instruments applicable to the study population that for the present research will consist of 168 students belonging to the Barreiro Educational Unit, of which only 120 will be considered. The results obtained showed that 57% of the students agree that digital resources should always be used as part of the tools for the development of project-based learning. Concluding that digital resources currently represent a necessary tool for the development of the teaching-learning process, motivating students to participate in the construction of their knowledge and the solution of environmental problems with the inclusion of project-based learning.